2020
DOI: 10.1002/aqc.3445
|View full text |Cite
|
Sign up to set email alerts
|

From individual vital rates to population dynamics: An integral projection model for European native oysters in a marine protected area

Abstract: Following an 85% decline in global oyster populations, there has been a recent resurgence in interest in the restoration of the European native oyster Ostrea edulis. Motivations for restoration from environmental stakeholders most often include recovering lost habitats and associated biodiversity and supporting ecosystem function. In coastal communities, another important justification is recovery of traditional and low‐impact fisheries but this has received less attention. Many restoration projects across Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 39 publications
(65 reference statements)
0
14
0
Order By: Relevance
“…Thus, alternative sources of information are needed if recent changes are to be investigated. Although recent analyses have shown that the Swedish population of the European flat oyster is still relatively healthy with densities and population size being rather substantial compared to populations at other European locations (Thorngren et al, 2019; for other examples of remaining strong populations of Ostrea edulis , see Allison et al, 2020, Lown et al, 2020), it is still affected. Using an ensemble modeling approach and field data of presence and abundance of living Ostrea edulis and empty shells, this study demonstrates an example of how empty shells of living organisms can be used for prediction of recent (8–15 years) changes in spatial distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, alternative sources of information are needed if recent changes are to be investigated. Although recent analyses have shown that the Swedish population of the European flat oyster is still relatively healthy with densities and population size being rather substantial compared to populations at other European locations (Thorngren et al, 2019; for other examples of remaining strong populations of Ostrea edulis , see Allison et al, 2020, Lown et al, 2020), it is still affected. Using an ensemble modeling approach and field data of presence and abundance of living Ostrea edulis and empty shells, this study demonstrates an example of how empty shells of living organisms can be used for prediction of recent (8–15 years) changes in spatial distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Recent analyses of the population of the European flat oyster, Ostrea edulis, in the Swedish Skagerrak area have shown that, despite its peripheral location in relation to the species’ biogeographic distribution, the densities and population size in this region are substantial compared with other European locations (Thorngren et al., 2019; for other examples of remaining strong populations of O. edulis see Allison et al., 2020; Lown et al., 2020). These analyses also demonstrated strong spatial variability in abundance within the area and, importantly, that rare high‐density oyster beds contribute disproportionally to the total population size.…”
Section: Discussionmentioning
confidence: 99%
“…Although the overall fishing pressure is currently low, there are no guarantees against complete removal of local populations following an agreement with a landowner under the current Swedish regulations. Thorngren et al (2019) estimated that the yearly harvest of O. edulis, mainly collected by hand, is <1% of the adult population in Sweden which is well within the limit of harvest (~5%) to still sustain a viable oyster population (Lown et al, 2020). Thus, the overall level of exploitation appears to be largely sustainable, although the status of individual oyster beds still needs to be protected from overfishing, anchoring, and other potential causes of degradation as destruction and loss of dense beds may cause severe and irreversible damage or slow recovery (Berghahn & Ruth, 2005;Eno et al, 2013), both as a consequence of reduced availability of settlement substrate and reduced broodstock densities (Guy et al, 2018;Korringa, 1952).…”
Section: Gigasmentioning
confidence: 99%
“…Protection of high-density oysters as "beds" could create unnecessary conflict due to policy implications of native oysters as a species versus a habitat regarding fishery management. This conflict can be minimized through adaptive and spatial management, and consideration that ecological restoration and fishery "recovery" are two different but complementary achievable objectives (Lown et al, 2020). Our study does not yet incorporate other ecosystem services (e.g., denitrification or fish nursery or foraging habitat potential) or minimum densities for successful reproduction, which may also affect the oyster density thresholds at which benefits to society accrue.…”
Section: Marine Sampling Challenges and Observing Real Density Dependent Biodiversity Relationshipsmentioning
confidence: 99%
“…Understanding where density thresholds for biodiversity associations may occur is also important in the context of forming management objectives about restoration (Guy, Smyth, & Roberts, 2019). If project aims are to boost biodiversity while supporting socioeconomic recovery of Ostrea oyster fisheries, or to increase sustainability of existing fisheries, adoption of density thresholds may be appropriate to restrict fishing when oyster densities approach those below which biodiversity may decline (KEIFCA, 2018; Lown, Hepburn, Dyer, & Cameron, 2020; McLeod et al, 2019).…”
Section: Introductionmentioning
confidence: 99%